Price, Product Quality, and Brand Image on Purchase Intention of Fashion Thrifting Products - Fifi Sihite; Sondang Nibulan Marbun; Tiur Rajagukguk; Rintan Saragih (Fakultas Ekonomi Universitas Simalungun, 2026)
This study investigates the effects of price, product quality, and brand image on the purchase intention of fashion thrifting products among Management Study Program students (Class of 2023) at Universitas Methodist Indonesia. A quantitative descriptive approach was employed, with a population of 250 students and a sample of 154 respondents selected using the Slovin formula. Data were gathered through Likert-scale questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. Findings reveal that price does not significantly influence purchase intention (sig. 0.266 > 0.05), whereas product quality exerts a positive and significant effect (sig. 0.003 < 0.05), and brand image demonstrates the strongest influence (sig. 0.000 < 0.05). Simultaneously, all three variables significantly predict purchase intention, yielding an F-value of 78.599 and an Adjusted R² of 60.3%. Brand image and product quality are identified as the primary drivers of student purchase intention toward fashion thrifting